Dynamics of Macroeconomy, Medicaid, and State Fiscal Conditions: A Role of Medicaid Expansion - Jang J; Lee KH (Dove Medical Press, 2023)
Jaeyoung Jang, Keon-Hyung Lee Askew School of Public Administration and Policy, Florida State University, Tallahassee, FL, USACorrespondence: Keon-Hyung Lee, Askew School of Public Administration and Policy, Florida State University, P.O. Box 3062250, 113 Collegiate Loop, Tallahassee, FL, 32306, USA, Tel +1-850-645-8210, Email klee2@fsu.eduBackground: One of the main concerns of state governments about Medicaid expansion is the potential increase in state fiscal burden following the rise in enrollments. In previous literature, limited attention has been paid to the effect of macroeconomic changes, which are closely linked to Medicaid enrollments, in understanding the impact of Medicaid expansion on a state. To narrow the gap, this study establishes a synthetic model to represent the transmission channel from an unemployment shock to the Medicaid program and state expenditures.Methods: The panel vector autoregression (VAR) model is adopted for the empirical analysis using annual data from 2010 to 2019 for 50 US states and D.C. The unit root and Granger causality tests are conducted to check the model's appropriateness. The estimated results are analyzed by using impulse response functions.Results: A sudden increase in the unemployment rate will raise the number of Medicaid enrollees and the state Medicaid expenditure, but the impact on the overall state budget is not clear. States that adopt Medicaid expansion will encounter surges in enrollment and increasing Medicaid expenditure during the economic recession, while the non-expansion states will only have moderate enrollment increases. However, an increased budgetary burden per new enrollees will not be significant at its level.Conclusion: Medicaid expansion will allow more people to benefit from the public health insurance program during an economic recession while the impact on states' fiscal burden will be moderate.Keywords: Medicaid expansion, state government finance, unemployment shock, panel vector autoregression, Medicaid enrollments